2016
DOI: 10.1007/s00391-016-1092-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of anemia with functional and nutritional status in the German multicenter study “GeriAnaemie2013”

Abstract: Polymedication and low serum albumin were independent risk factors for anemia in geriatric patients, probably reflecting disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“… 21 Preliminary results of the first German multi-center study on anemia prevalence among geriatric inpatients found a prevalence of >55% and confirmed the previous findings of the monocentric studies. 22 …”
Section: Anemia In the Agedmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 Preliminary results of the first German multi-center study on anemia prevalence among geriatric inpatients found a prevalence of >55% and confirmed the previous findings of the monocentric studies. 22 …”
Section: Anemia In the Agedmentioning
confidence: 99%
“… 18 This finding was confirmed by the German multicenter study on anemia prevalence among geriatric inpatients. 22 …”
Section: Anemia In the Agedmentioning
confidence: 99%
“…Our results also showed that patients with OPC had a higher incidence of critical weight loss and grade 3–4 anaemia than patients without OPC during RT. Weight loss and anaemia are commonly used indicators of malnutrition [ 24 – 26 ]. In cancer patients, a variety of factors, including the tumour, the host response to the tumour, and anticancer treatment, may cause malnutrition and cachexia [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although, polymedication was considered independent risk factor for anemia, a 12-35% higher chance of anemia was seen in aspirin users alone. Other drugs like corticosteroids and anti-acids were also seen associated with IDA [43,44]. Screening for under nutrition should be included in assessment of anemia in geriatric patients as low serum albumin levels are found as independent risk factors for anemia in geriatric patients [44,45].…”
Section: Etiopathogenesismentioning
confidence: 99%